Exosome biomarkers in cardiovascular diseases and their prospective forensic application in the identification of sudden cardiac death - Ye Wang; Jie Wang; Li Hu; Shuainan Huang; Yue Cao; Youjia Yu; Feng Chen (Wolters Kluwer Medknow Publications, 2022)
Sudden cardiac death (SCD) is a common cause of death due to the high prevalence and mortality of cardiovascular disease (CVD). Currently, the forensic identification of SCD relies on traditional histomorphological examination, lacking stable biomarkers with high specificity and sensitivity. Previous studies have shown that exosomes (Exos) are ideal vectors and the application of Exos provides novel insight as the diagnostic biomarkers and treatment of CVD, and is hot research filed in biomedicine. This review briefly describes the biology of Exos, including the biogenesis of Exos and the mechanisms of action. The research progresses on Exos multi-omics, i.e., genomics, proteomics and metabolomics, and their roles in the diagnosis of different types of CVD, especially coronary heart disease and cardiomyopathy, are summarized. In addition, the current difficulties of applications of Exos in forensic identification of SCD and the prospective forensic applications in the future are highlighted. The aim of this review is to summarize the current advances of Exos in CVD in a disease-oriented manner, and to provide a reference for future forensic pathological identification of SCD, as well as the early diagnosis of SCD in clinic.